2021
DOI: 10.3390/su131810263
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Characteristics and Driving Factors of Land-Use Changes in the Tarim River Basin from 1990 to 2018

Abstract: Land-use and cover change is an important indicator for exploring global change trends, with in-depth research on land use and its driving factors being of particular significance in forging ecologically sustainable development. The present work used the Tarim River Basin as the study area, while the land-use transfer matrix, normalized difference vegetation index (NDVI), regional center-of-gravity model, and night-time-light remote-sensing mutual correction method were employed to explore temporal and spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…With the expansion of cultivated land and construction land, the development and utilization of water resources have been strengthened; consequently, the water volume of the main stream of the Tarim River has been greatly reduced. Precipitation has been unable to meet water demand, resulting in a significant reduction in ecological land water areas (Wang et al, 2021), comprising a total reduction of 13,665.5622 km 2 during the study period. Moreover, industrialization, agricultural production, and other human activities require extensive water resources, which means that construction land is mostly distributed in areas close to roads and water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…With the expansion of cultivated land and construction land, the development and utilization of water resources have been strengthened; consequently, the water volume of the main stream of the Tarim River has been greatly reduced. Precipitation has been unable to meet water demand, resulting in a significant reduction in ecological land water areas (Wang et al, 2021), comprising a total reduction of 13,665.5622 km 2 during the study period. Moreover, industrialization, agricultural production, and other human activities require extensive water resources, which means that construction land is mostly distributed in areas close to roads and water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…NTL has already been used to extract [36] and identify tourist attractions [37]. Ecological quality has been closely linked to tourism development; therefore, NTL data are used to study ecological changes [38]. As the accessibility of tourism POI data gradually improved, it was found that the POI of tourism factors had a significant influence on the difference in the spatial distribution of NTL [39]; the spatial coupling between the two is good.…”
Section: Introductionmentioning
confidence: 99%
“…Its application to geography began with calculating the population center of gravity, expressed through latitude and longitude coordinates. By using a migration model based on the center of gravity, we could simulate temporal changes in carbon emissions' center of gravity, providing a more intuitive representation of their spatial and temporal dynamics within the study area [46]. To investigate China's changing carbon emissions patterns, this model was used to calculate the carbon emissions' center of gravity between 2000 and 2019.…”
Section: Center Of Gravity Migration Modelmentioning
confidence: 99%